Control of Salmonella in low-moisture foods: Enterococcus faecium NRRL B-2354 as a surrogate for thermal and non-thermal validation. Issue 21 (19th July 2022) - Dhowlaghar, Nitin; Zhu, Mei-Jun
Abstract: Salmonella has been implicated in multiple foodborne outbreaks and recalls associated with low water activity foods (Law F). To verify the effectiveness of a process against Salmonella in Law F, validation using a nonpathogenic surrogate strain is essential. Enterococcus faecium NRRL B-2354 strain has been used as a potential surrogate of Salmonella in different processing of Law F. However, the survival of Salmonella and E. faecium in Law F during food processing is a dynamic function of aw, food composition and structure, processing techniques, and other factors. This review assessed pertinent literature on the thermal and non-thermal inactivation of Salmonella and its presumable surrogate E. faecium in various Law F and provided an overview of its suitibility in different Law F. Overall, based on the D-values, survival/reduction, temperature/time to obtain 4 or 5-log reductions, most studies concluded that E. faecium is a suitable surrogate of Salmonella during Law F processing as its magnitude of resistance was slightly greater or equal (i.e., statistical similar) as compared to Salmonella . Studies also showed its unsuitability which either does not provide a proper margin of safety or being overly resistant and may compromise the quality and organoleptic properties of food. This review provides useful information and guidance for future validation studies of Law F.